2019
DOI: 10.1007/978-3-030-22871-2_65
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Various Machine Learning Models for Multi-class Classification of RNA-Seq Expression Data

Abstract: Late diagnosis and high costs are key factors that negatively impact the care of cancer patients worldwide. Although the availability of biological markers for the diagnosis of cancer type is increasing, costs and reliability of tests currently present a barrier to the adoption of their routine use. There is a pressing need for accurate methods that enable early diagnosis and cover a broad range of cancers. The use of machine learning and RNA-seq expression analysis has shown promise in the classification of c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…In general, in all simulated datasets, the classification performance of RF outperforms the CART, LR and SVM. It is in line with the previous studies [31,32,33]. RF algorithm had been previously shown to perform outstanding in several bioinformatics tasks [34].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In general, in all simulated datasets, the classification performance of RF outperforms the CART, LR and SVM. It is in line with the previous studies [31,32,33]. RF algorithm had been previously shown to perform outstanding in several bioinformatics tasks [34].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, RF can handle the overdispersion relatively better than the other algorithms. RF is one of ensemble methods which aggregates multiple machine learning models with the aim of decreasing both bias and variance [32,33]. Hence, the result from an ensemble method such as RF will be better than any of individual machine learning model.…”
Section: Discussionmentioning
confidence: 99%
“…First, to categorise cancer, Sterling Ramroach et al used various machine learning techniques [18]. A dataset for several cancer kinds was downloaded for their study from the online data portal COSMIC.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, Cascade forests are built using decision treebased random forests trained to find relevant characteristics in raw data. Next, this result was placed against state-of-the-art classifiers like SVM, KNN, LR, RF, and the original gcforest [18]. The authors claimed that their suggested approach produced more precise results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The state of a cell communicated by the layout of RNA will thusly serve to be of great help to check whether a cell might be a normal or a variation one [15]. The use of machine learning in cancer diagnosis is becoming more feasible as algorithms become less prone to error and noise, and as the volume of training data increases [16]. The proposed SVM and KNN methods are tested and the accuracy of both the approaches are recorded as 71.52% and 94.74%, respectively.…”
Section: Related Workmentioning
confidence: 99%